2015
DOI: 10.5423/ppj.oa.03.2015.0044
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Detection Method for Potato virus X by Reverse Transcription Loop-Mediated Isothermal Amplification

Abstract: The primary step for efficient control of viral diseases is the development of simple, rapid, and sensitive virus detection. Reverse transcription loop-mediated isothermal amplification (RT-LAMP) has been used to detect viral RNA molecules because of its simplicity and high sensitivity for a number of viruses. RT-LAMP for the detection of Potato virus X (PVX) was developed and compared with conventional reverse transcription polymerase chain reaction (RT-PCR) to demonstrate its advantages over RT-PCR. RT-LAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Deoxynucleoside Triphosphate (dNTP) is source of nucleotides for amplification of target template DNA. Jeong et al (2015) cited that the amplified LAMP products were obtained using a concentration of dNTPs ranging from 0.4 to 1.4 mM, but no reaction products were obtained at 0.2 mM. Betaine (N,N,N-trimethyl glycine) is routinely used in LAMP amplification to lower the melting temperature, increase the specificity and facilitate the separation of DNA templates (En et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Deoxynucleoside Triphosphate (dNTP) is source of nucleotides for amplification of target template DNA. Jeong et al (2015) cited that the amplified LAMP products were obtained using a concentration of dNTPs ranging from 0.4 to 1.4 mM, but no reaction products were obtained at 0.2 mM. Betaine (N,N,N-trimethyl glycine) is routinely used in LAMP amplification to lower the melting temperature, increase the specificity and facilitate the separation of DNA templates (En et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the combinations of low concentration IBA and NAA were effective for root growth, this was probably because IBA was the most effective treatment in causing root elongation, whereas NAA was effective for increasing the number of roots [19]. Meantime, it is reported that the optimum culture conditions for the growth of Panax ginseng adventitious roots were likely to be 3/4 medium salt strength, 6% sucrose, and 5 g/L inoculum density [23,24]. Medium salt strength is a critical determinant in controlling the growth of adventitious roots [25].…”
Section: Optimization Of Culture Conditions In Adventitious Rootsmentioning
confidence: 92%
“…Considering the capability of TaqMan real-time RT-PCR to discriminate small sequence it was found to be the most useful, practicable technique (Singh et al 2013), and using a quadruplex real-time RT-PCR, PLRV, PVA, PVX, and PVY can be detected simultaneously (Jeong et al 2015). Optimum dilution, inhibition of RNAses, and the optimization of RT-PCR steps are critical factors that influence the detection of these four viruses from dormant potato tubers (Agindotan et al 2007).…”
Section: Development Of Real-time Pcr For Potato Virus Detectionmentioning
confidence: 99%
“…Furthermore, for field testing, due to its closed-tube format, the LAMP has been found to be able to control substances that can inhibit PCR reaction so that allowing the technique to be used with simple protocols of genetic materials amplification (Kaneko et al 2007). Ju (2011) showed RT-LAMP as an extremely efficient, sensitive, accurate, simple, fast and reliable detection tool for (Jeong et al 2015) PLRV detection within potato tubers. After visual detection of PLRV by a LAMP with the Gene Finder™ dye, it has been an open door for plant pathology in general (Almasi et al 2013).…”
Section: The Development Of Isothermal Amplification For Potato Virusmentioning
confidence: 99%